Circadian clock disruptions link oxidative stress and systemic inflammation to metabolic syndrome in obstructive sleep apnea patients - Li, Xiaoming; Liu, Xuejian; Meng, Qiu; Wu, Xinhao; Bing, Xin; Guo, Na; Zhao, Xuening; Hou, Xiaozhi; Wang, Baowei; Xia, Ming; Li, Hui (Frontiers in Physiology, 2022)
Objectives: Obstructive sleep apnea (OSA) is an independent risk factor for metabolic syndrome (MetS). Recent studies have been indicated that circadian clock genes were dysregulated in OSA. Additionally, it is clear that impairment of circadian clocks drive the progression of MetS. Therefore, we hypothesized that circadian rhythm disruption links OSA with MetS. Methods: A total of 118 participants, who underwent polysomnography (PSG) and diagnosed as healthy snorers (control, n=29) or OSA (n=89) patients based on the apnea-hypopnea index (AHI), were enrolled in the present study. General information, anthropometric data, blood biochemical indicators, clock gene expressions, levels of oxidative and inflammatory indicators were collected, determined and compared in all the participants. Results: We found that Brain and muscle aryl hydrocarbon receptor nuclear translocator-like protein 1 (Bmal1) and Differentiated embryo chondrocyte 1 (Dec1) were upregulated, while Period 1 (Per1) was reduced in OSA patients. In addition, these changing trends were closely associated with the hypoxia indicator of AHI and have a significant impact on presence of MetS components, such as hyperglycemia (Dec1 and Per1, P＜0.05 and 0.001, respectively), hypertension (Bmal1 and Dec1, P＜0.001 and 0.01, respectively), hyperlipidaemia (Dec1, P＜0.01), and obesity (Dec1, P＜0.05). Notably, expressions of Dec1 correlated of IR and predicted the presence of MetS in OSA patients. Finally, we also observed that Dec1 expression was interrelated with levels of both oxidative indicators and inflammatory biomarkers (IL-6) in OSA. Conclusion: This study concluded that circadian clock disruptions, specially Dec1, link OSA with MetS in an oxidative and inflammatory related manner. Circadian clock Dec1 can be used as a specific biomarker (P＜0.001) and therapeutic target in OSA combined with Mets patients.